2017
DOI: 10.1108/jm2-07-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the key barriers to lean construction using interpretive structural modeling

Abstract: Purpose The purpose of this study is to identify and analyze the key barriers to lean implementation in the construction industry using interpretive structural modeling (ISM) and Matrice d’ Impacts Croisés-Multiplication Appliquée á un Classement (MICMAC) analysis. Design/methodology/approach In this study, 13 barriers to lean construction (LC) have been identified through extensive review of literature and subsequently eliciting expert opinions. A proper hierarchy and contextual relationship of the barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 62 publications
1
42
0
2
Order By: Relevance
“…However, even though the construction industry has improved its processes and results through LC, as shown by Dunlop and Smith (2004), Yu et al (2011), Pheng and Lin (2015), Ruppenthal et al (2015), reports described in works such as Koskela et al (2002), Bajjou and Chafi ( 2018), Ahmed and Sobuz (2019), Sarhan et al (2017), Khaba and Bhar (2016), Martinez et al (2019) point to barriers that hinder the development and diffusion of LC, some of which are presented in Section 4.…”
Section: Barriers Evaluation To Lean Constructionmentioning
confidence: 99%
“…However, even though the construction industry has improved its processes and results through LC, as shown by Dunlop and Smith (2004), Yu et al (2011), Pheng and Lin (2015), Ruppenthal et al (2015), reports described in works such as Koskela et al (2002), Bajjou and Chafi ( 2018), Ahmed and Sobuz (2019), Sarhan et al (2017), Khaba and Bhar (2016), Martinez et al (2019) point to barriers that hinder the development and diffusion of LC, some of which are presented in Section 4.…”
Section: Barriers Evaluation To Lean Constructionmentioning
confidence: 99%
“…Almeida Marodin and Saurin (2015) developed a framework for proper implementation of LM and subsequently analyzed the common barriers using the interpretive structural modeling (ISM) approach. Khaba and Bhar (2017) analyzed the key barriers to lean practices in construction industries by using ISM methodology and found that “cultural differences” are the most critical barriers in adoption of these practices. Jadhav et al (2014) examined 12 common barriers to the implementation of JIT production through the ISM approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the help of expert opinion, ISM can be used for drawing the interrelationships between unstructured and poorly communicated variables (Mandal and Deshmukh, 1994). Researchers are using ISM technique in various fields such as supply chain management (Gorane and Kant, 2015; Kumar and Rahman, 2017), lean construction (Khaba and Bhar, 2017), environmentally conscious manufacturing (Kumar Mittal and Singh Sangwan, 2014), sustainable supplier selection (Girubha et al , 2016), environmentally concerned consumer behaviour (Kautish and Dash, 2017), green supply chain management (Gardas et al , 2018) and total productive maintenance implementation (Singh et al , 2014). ISM is a sequential process, various steps of ISM are shown in Figure 1 (Warfield, 1974; Mahajan et al , 2014).…”
Section: Methodsmentioning
confidence: 99%